DESIGN OF AIRPORT CITY IN KULON PROGO INTERNATIONAL AIRPORT YOGYAKARTA - AYU SAWITRI DIAN MAWARNI (NIM : 25613004), IDA
Airports now not only serve as an infrastructure of the city. Non-aeronautic activity of airports has more economic potential than the aeronautic activity. High quantity of movement in airports creates business opportunities to both tourist and investor. This increase in movement will soon make old airports in urban areas overloaded with no room for further development, thus triggering new airport developments in empty sub urban areas. This new area will be affected by the development force from the high increase of movements then the airport will be a new city center and create an Ã‚Â“airport city'. The character of this airport city will be determined by the type of airport developed and local potentials, which in the case of this thesis is the Kulon Progo International Airport in Yogyakarta and the local potential of Yogyakarta as a city. A study on the characteristic of Yogyakarta, a city famous for its strong local culture is used as the main design approach. Market analysis and hierarchy process analysis then are used to create the facility program. The design process of this airport city of Yogyakarta starts with a planning process by appreciating the context, followed by creating the urban structure, making connections, and detailing the place. Design concepts used are the result of the facility programming analysis and a study of design criteria of airport city, synthesized from land development, mixed use development, and airport development literature. The design concept consists of three aspects of airport city design; airport central business district, impression of destination, and airport city character. The central business district design aspect will cover the master plan concept, facility programming concept, and development phasing concept, and are based on synergy planning and cultural representation. Impression of destination design aspect will cover the gate concept, circulation concept, and accessibility concept, and are based on efficiency and Javanese spatial experience. Airport city character design aspect will cover the prime, supporting, and necessary facility concept, and are based on Javanese spatial arrangement.